Electronically Tunable Dual-Input Integrator Employing a Single CDBA and a Multiplier: Voltage Controlled Quadrature Oscillator Design - R. Nandi; Mousiki Kar; Sagarika Das (Active and Passive Electronic Components)
A new dual-input differential input active integrator using a current differencing buffered amplifier (CDBA) is proposed. A multiplier element is appropriately used in the circuit whose control voltage (Vc) tunes the integrator time constant (τ) electronically. The design of a voltage controlled quadrature oscillator (VCQO) based on the proposed integrator had been satisfactorily implemented. A new type of measurement for the tuning error of the oscillator based on the Nyquist plot is presented that shows an error of only 2% at fo≈ 1 MHz with Total Harmonic Distortion (THD) less than 3%.